Uma flecha não bastou para calar a sua voz: a comunidade de Bom Jesus em cena - MORAES, Raimunda da Silva (2019)
The present work of Course Conclusion aims to record the memories of the community of Bom Jesus of the municipality of Santo Antônio do Tauá / PA, from the festivity of São Sebastião. Our conducting are the memories of the actions of Job Barbosa, who on receiving the image of St. Sebastian from his father, initiated a religious, cultural and social life in the locality, through litanies, revelry, pajelança and festivity. The methodological and theoretical paths are Oral History and Memory Studies, such as Bosi (1994), Freitas (2002), Fernandes (2011) and Thompson (1992), who assisted us in the collection of data, And in the reflection of the collective memories, which present themselves through the coexistence of the community in a group, and the individual ones that are personal memories, fundamental for the accomplishment of the scenic activity of this research process. Thus, the testimonies and reports of residents of Bom Jesus, made during the period from 2013 to 2016, were extremely important, since they experienced these manifestations, contributing significantly to the process of this work. I thus understand that it is possible to cross these elements by articulating a bond with the memories of a place and a family that help in the reconstruction of a past and emphasize stories of the present that also become memories.